Effect of Melatonin on Increasing the Effectiveness of Liver Preservation Solution - Erdoğan, Mehmet Mustafa; Erdemli, Mehmet Erman; Özhan, Onural; Erdemli, Zeynep; Gözükara Bağ, Harika Gözde; Vardı, Nigar (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Various tissue preservation solutions are used during the removal of the organ and during transplantation to protect the normal histological and biochemical characteristics of tissue while performing a successful liver transplant. In our study, it was aimed to investigate the effects of intraperitoneal melatonin administration on liver preservation damage before transplantation. Materials and Methods: In our study, the histological and biochemical characteristics of University of Wisconsin+melatonin group rats treated with melatonin 45 minutes before hepatectomy were compared between serum physiologic group and University of Wisconsin group. Results: When hematoxylin and eosin staining was evaluated in terms of hydropic degeneration, sinusoidal dilatation, and hepatocyte necrosis, there was no statistically significant difference. Caspase 3 immunohistochemical staining showed a significant increase in Caspase 3 immunoreactivity positivity at the 12th-hour University of Wisconsin group compared to University of Wisconsin+melatonin group. As a result of biochemical analysis, the malondialdehyde and total oxidant status levels in the University of Wisconsin+melatonin group decreased significantly compared to the University of Wisconsin group. When the reduced glutathione activity and total antioxidant capacity level were compared, a significant increase was observed in the University of Wisconsin+melatonin group compared to the University of Wisconsin group at the 12th hour. It was also found that aspartate aminotransferase, alanine aminotransferase, and alkaline phosphatase levels decreased significantly in the University of Wisconsin+melatonin 12th-hour group compared to the University of Wisconsin 12th hour and control group. Conclusion: When the findings were evaluated, intraperitoneal administration of melatonin, a cytoprotective antioxidant, was found to play an effective role in preserving immunohistochemical and biochemical properties of liver tissue integrity and hepatocytes in University of Wisconsin solution. Cite this article as: Erdoğan MM, Erdemli ME, Özhan O, Erdemli Z, Gözükara Bağ HG, Vardı N. Effect of melatonin on increasing the effectiveness of liver preservation solution. Turk J Gastroenterol. 2023;34(9):943-951.